PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. PATRA BADAK ARUN SOLUSI - Imam Arrywibowo; Tamzil Yusuf; Nurhayati Nurhayati (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The purpose of this research is to determine the influence of compensation, motivation and work discipline on employee job satisfaction at PT. Patra Badak Arun Solutions Balikpapan. Data collection was carried out through distributing questionnaires targeting 52 PT employees. Patra Badak Arun Solutions Balikpapan. The research methodology uses a quantitative approach and uses purposive sampling. Statistical tests and data processing were carried out using Partial Least Square (PLS) via the SmartPLS version 3.0 program. Research findings reveal that motivation variables have a positive and significant influence on job satisfaction. On the other hand, compensation and work discipline variables do not have a significant effect on job satisfaction.